GAMBARAN TINGKAT PENGETAHUAN TENTANG PENTINGNYA KONSUMSI SERAT UNTUK MENCEGAH KONSTIPASI PADA MASYARAKAT KELURAHAN RENGAS CONDONG KECAMATAN MUARA BULIAN /KABUPATEN BATANGHARI PROVINSI JAMBI - Elsa Nadhia Amanda; Debie Anggraini; Dita Hasni; Sri Nani Jelmila (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Background: Dietary fiber is part of food in the form of complete carbohydrates found in plant cell walls and can be consumed by the body. People who consume low fiber will slow down the transit time of food in the intestine which will cause constipation. Constipation is the sensation or desire to have a bowel movement, feeling dissatisfied with bowel movements, pain, needing extra pressure or having a hard bowel movement. Constipation is also said to be in everyday situations when defecating is less than 3 times a week and defecating is required by straining excessively. Objective: To describe the level of knowledge about the importance of fiber consumption to prevent constipation in the people of Rengas Condong Village, Muara Bulian District Batanghari Regency, Jambi Province in 2021. Methods: The type of research used is descriptive with a crosssectional approach. The affordable population in this study were the people of Rengas Condong Village, Muara Bulian District, Batanghari Regency, Jambi Province with 148 samples using simple random sampling. Univariate data analysis is presented in the form of frequency distribution and percentage and data processing using the computerized SPSS version 25.0 program. Results: Most errors in knowledge are in statement number 8, namely water-soluble fiber is easily digested (89.9%), the most gender were male, namely 76 people (51.4%) and the most recent age was late adulthood, namely 37 people (25.0%), and the highest level of knowledge was moderate, namely 101 people (68.2%) Conclusion: Error The most knowledge in statement number 8 is that water-soluble fiber is easy to digest, the most sexes are male and the age at most is late adulthood, and the most knowledge level is moderate.